Optically pumped lasing properties of InGaN/GaN stripe multiquantum wells with ridge cavity structure on patterned (001) Si substrates. (29th January 2015) - Kushimoto, Maki; Tanikawa, Tomoyuki; Honda, Yoshio; Amano, Hiroshi
Abstract: We demonstrated lasing action and investigated the optical properties of multiquantum-well (MQW) stripe crystals on patterned (001) Si substrates. Longitudinal and higher order transverse modes were observed from a ridge waveguide structure. These results strongly suggest the possibility of fabricating InGaN MQW laser diodes on (001) Si.